proceedings of the round table conference on distance education for south Asian countries, 6-8 November 1989, Islamabad, Pakistan (Islamabad, 1990)
This document begins with an introduction followed by a list of recommendations that were an outcome of the conference. The core papers included are "Liberation of the Learner: A Self-Reliance Strategy for Education" (Sharma); "Distance Education in South Asia: Problems and Strategies for Cooperation" (Taylor); "Cooperation in Distance Education in South Asian Countries" (Marchl); and "Teacher Training and Staff Development" (Edington). Country paper summaries are provided for Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan, and Sri Lanka. The appendices contain: the opening address (Juneja); keynote address (Qazi); group reports; list of participants; list of observers; and a list of organizing and resource persons. (CML)
Keywords: Distance education; South Asia